Concurrent validity of inertial measurement unit for the assessment of countermovement jump in youth soccer - Cortis, C.; Picerno, P.; Pesce, C.; Capranica, L. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Countermovement jump (CMJ) is considered a suitable test to determine muscle power, a good indicator of functional performance and a relevant index in soccer (Wisloff et al., 2004; Holsgaard et al., 2007), reflecting the players` ability to perform stretchshortening cycle activities. In field conditions, CMJ measurements are usually performed by means of optical cells and contact mats, which can only be used on a flat surface, limiting the ecological validity of the evaluation when investigating athletes who compete on different surfaces (i.e., clay, artificial turf, natural grass). Thus, the aim of this study was to evaluate concurrent validity and reliability of wearable accelerometers with photocell system measurements for measuring flight time, thus estimating vertical jump height. Methods: After obtaining parental, club and coach informed consent forms, 14 young elite ("Esordienti" team of the Italian first league S.S. Lazio Club) soccer players (age: 12±1 years; body mass: 40.3±9.1 kg; height: 151.9±11.8 cm; BMI: 19.1±1.3) were asked to perform maximal countermovement jumps (CMJ). To evaluate concurrent validity, athletes` CMJ flight times were recorded by means of an inertial measurement unit (IMU, FreePower Jump Module, Sensorize, Italy) wore on the trunk at the level of L5 and, at the same time by means of Optojump photocells (Microgate, Italy) considered as a goal standard (Glatthorn et al., 2011). To investigate test-retest reliability of the IMU, athletes participated in two experimental sessions separated by one week. Repeated measures ANOVA (p<0.05) was used to evaluate differences in experimental sessions. Intra-class correlation coefficients (ICCs) were used to evaluate validity and reliability. Results: No differences emerged between experimental sessions (Test: Optojump = 0.448±0.027 s; IMU = 0.471±0.021 s; Retest: Optojump = 0.455±0.026 s; IMU = 0.478±0.022 s). High (p<0.001) ICCS were found between measurement systems for both experimental sessions (test = 0.891; retest = 0.959). Furthermore, IMU system showed an excellent test-retest reliability (ICC = 0.976). Discussion The IMU system demonstrated good concurrent validity and excellent test-retest reliability for the measurement of flight time in young soccer players. Therefore, this tool can be used as a valid method to measure CMJ flight time to estimate jump height in field settings, independently from testing surface, thus improving the ecological validity of the measurement.